Controlling Cu–Sn mixing so as to enable higher critical current densities in RRP® Nb3Sn wires. (25th April 2018) - Sanabria, Charlie; Field, Michael; Lee, Peter J; Miao, Hanping; Parrell, Jeff; Larbalestier, David C
Abstract: Dipole magnets for the proposed Future Circular Collider (FCC) demand specifications significantly beyond the limits of all existing Nb3 Sn wires, in particular a critical current density ( J c ) of more than 1500 A mm −2 at 16 T and 4.2 K with an effective filament diameter ( D eff ) of less than 20 μ m. The restacked-rod-process (RRP ® ) is the technology closest to meeting these demands, with a J c (16 T) of up to 1400 A mm −2, residual resistivity ratio > 100, for a sub-element size D s of 58 μ m (which in RRP ® wires is essentially the same as D eff ). An important present limitation of RRP ® is that reducing the sub-element size degrades J c to as low as 900 A mm −2 at 16 T for D s  = 35 μ m. To gain an understanding of the sources of this J c degradation, we have made a detailed study of the phase evolution during the Cu–Sn 'mixing' stages of the wire heat treatment that occur prior to Nb3 Sn formation. Using extensive microstructural quantification, we have identified the critical role that the Sn–Nb–Cu ternary phase ( Nausite ) can play. The Nausite forms as a well-defined ring between the Sn source and the Cu/Nb filament pack, and acts as an osmotic membrane in the 300 °C–400 °C range—greatly inhibiting Sn diffusion into the Cu/Nb filament pack while supporting a strong Cu counter-diffusion from the filament pack into the Sn core. This converts the Sn core into a mixture of the low melting point (408 °C) η phase (Cu6 Sn5 ) and the more desirable ε phase (Cu3 Sn), which decomposes at 676 °C. After the mixing stages, when heated above 408 °C towards the Nb3 Sn reaction, any residual η liquefies to form additional irregular Nausite on the inside of the membrane. All Nausite decomposes into NbSn2 on further heating, and ultimately transforms into coarse-grain (and often disconnected) Nb3 Sn which has little contribution to current transport. Understanding this critical Nausite reaction pathway has allowed us to simplify the mixing heat treatment to only one stage at 350 °C for 400 h which minimizes Nausite formation while encouraging the formation of the higher melting point ε phase through better Cu–Sn mixing. At a D s of 41 μ m, the Nausite control heat treatment increases the J c at 16 T by 36%, reaching 1300 A mm −2 (i.e. 2980 A mm −2 at 12 T), and moving RRP ® closer to the FCC targets.